Qualidade da água de mananciais empregados na irrigação e lavagem de hortaliças da região de Apucarana, Paraná - Vilela, Vera Lúcia Delmônico (2018)
The activity of irrigation and washing of vegetables ingested in natura such as leafy vegetables, can transmit pathogenic microorganisms, in this context, the monitoring of water quality is fundamental to determine its framing and destination. The bacterium Escherichia coli is used as a tool to evaluate fecal contamination of water resources. In this sense, the objective of this research was to evaluate the microbiological and physicochemical quality of water intended for irrigation and washing of vegetables in rural properties in the region of Apucarana, Paraná. In the months of july and september water samples were collected in 9 properties that make use of surface and underground springs for irrigation and vegetable washing. A questionnaire was applied to the producers to collect data regarding the management of the production and destination of the cultivated products. The MTEC Acumedia Agar filter membrane technique was used for quantification and identification of E. coli and other bacteria with pathogenic potential. For the differentiation and isolation of the bacteria of interest, Difco CHROMagar Orientation medium was used. The indicative colonies with pathogenic potential were isolated and submitted to biochemical tests, susceptibility to antibiotics and chlorinated sanitizers and acetic acid. Physicochemical parameters such as pH, temperature, dissolved oxygen, total solids, turbidity, nitrite and nitrate were evaluated. Of the 36 samples evaluated, E. coli contamination was found in 72%, E. cloacae in 83% and E. faecalis in 2.8%. Antimicrobial susceptibility tests showed mostly sensitive E. coli isolates, however resistance to Ampicillin, Tetracycline and Chloramphenicol was observed, determining the bacterial resistance. Resistance to Ampicillin and Tetracycline was verified by E. cloacae and E. faecalis. The best performance sanitizer was 1:60 (200 ppm) bleach, the food disinfectant and the vinegar showed little or no action on the microorganisms. The physical and chemical parameters were compatible with CONAMA Resolution 357/05 and 396/08 for class I waters, except for the OD parameters at P6 and P7 and the turbidity that indicated 43 UNT at P7 in irrigation water. Only the irrigation and lavage waters of P5 are suitable for the purpose proposed during the two evaluated periods. The other points did not meet the criteria recommended by the legislation in at least one of the evaluated periods.